ASSOCIATION OF MIGRAINE AND ATRIAL FIBRILLATION : A TEN YEARS SYSTEMATIC REVIEW - S Halim, Stevanie; Ayu Zaskia, Nanda (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Migraine is a primary headache that can present with several neurological and autonomic symptoms, which generally occurs in young to middle-aged women. When accompanied by aura, migraines have a major impact on quality of life due to the severity of the symptoms. The aim: This study aims to show association of migraine and atrial fibrillation. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 41 articles, whereas the results of our search on SagePub brought up 135 articles. The results of the search conducted for the last year of 2013 yielded a total 26 articles for PubMed and 50 articles for SagePub. The result from title screening, a total 2 articles for PubMed and 19 articles for SagePub. In the end, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: Migraine is associated with an increased risk of myocardial infarction, ischemic stroke, hemorrhagic stroke, venous thromboembolism, and atrial fibrillation and atrial flutter. Migraine is an important risk factor for most cardiovascular diseases.